Current perspectives of artificial oxygen carriers as red blood cell substitutes: a review of old to cutting-edge technologies using in vitro and in vivo assessments - Mohanto, Nijaya; Park, Young Joon; Jee, Jun Pil (Journal of Pharmaceutical Investigation, 2023)
Background: Several circumstances such as accidents, surgery, traumatic hemorrhagic shock, and other causalities cause major blood loss. Allogenic blood transfusion can be resuscitative for such conditions; however, it has numerous ambivalent effects, including supply shortage, needs for more time, cost for blood grouping, the possibility of spreading an infection, and short shelf-life. Hypoxia or ischemia causes heart failure, neurological problems, and organ damage in many patients. To address this emergent medical need for resuscitation and to treat hypoxic conditions as well as to enhance oxygen transportation, researchers aspire to achieve a robust technology aimed to develop safe and feasible red blood cell substitutes for effective oxygen transport. Area covered: This review article provides an overview of the formulation, storage, shelf-life, clinical application, side effects, and current perspectives of artificial oxygen carriers (AOCs) as red blood cell substitutes. Moreover, the pre-clinical (in vitro and in vivo) assessments for the evaluation of the efficacy and safety of oxygen transport through AOCs are key considerations in this study. With the most significant technologies, hemoglobin- and perfluorocarbon-based oxygen carriers as well as other modern technologies, such as synthetically produced porphyrin-based AOCs and oxygen-carrying micro/nanobubbles, have also been elucidated. Expert opinion: Both hemoglobin- and perfluorocarbon-based oxygen carriers are significant, despite having the latter acting as safeguards; they are cost-effective, facile formulations which penetrate small blood vessels and remove arterial blockages due to their nano-size. They also show better biocompatibility and longer half-life circulation than other similar technologies.
Keywords: Artificial oxygen carriers; In vitro and in vivo assessment; Old to cutting-edge technologies; Red blood cell substitutes